Teaching Vocabulary Using Visual Media and TPR for Early Childhood Learners - Arvan Permana Habib; Fahriany, Fahriany (Charta Educa: Jurnal Kajian Pendidikan, 2025)
The aim of this research is to investigate how visual media and TPR instructions helped very young learners learn English vocabularies. Young learners are typically the students who are generally enrolled in kindergarten and elementary schools, typically range from five or six to around 12 years old. In educational field, knowledge and understanding of ways are needed to improve the effectiveness of the educational practices for young learners. The research was a qualitative research utilizing narrative inquiry. The subjects in this research were a K-1 kindergartener pupil and a second grade pupil of elementary school. The data was taken by creating field notes. The students created meaning of vocabularies by identifying the visual media. The students sometimes would ask directly what it means. With TPR instructions, the subjects’ knowledge developed their knowledge demonstrated by the subjects’ ability to follow the action that involved the vocabularies that were discussed.